1959
DOI: 10.1017/s0007485300054481
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Stomoxys calcitrans (L.) in Uganda, East Africa.

Abstract: The importance of certain species of Stomoxys in Uganda, the possibility that these species may be responsible for the mechanical transmission of trypanosomiasis, and the effects of severe biting of Stomoxys on cattle causing loss in milk yields and weight in beef animals, is pointed out.A satisfactory method is described for rearing large numbers of Stomoxys calcitrans (L.) under the conditions that prevail in East Africa.A description of special cages for keeping the adults and for egg production is given, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1962
1962
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Interestingly, the flying insects such as dragonflies are a good resource base for migrant birds (Brown et al 1982;Fry et al 2000Fry et al , 2004, hence the link between birds and insects as indicators of rainfall seasonality. Entomological studies done in the Rwenzori region in Western Uganda showed that Stomoxys calcitrans breed during the onset of rains but are adversely affected by the dry season (Kangwagye 1974;Parr 1959). The onset of rains provides good conditions in open grazing areas with moist rotted dung that enables eggs to hatch and the pupae to emerge into adult flies (Parr 1959).…”
Section: ) Insectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the flying insects such as dragonflies are a good resource base for migrant birds (Brown et al 1982;Fry et al 2000Fry et al , 2004, hence the link between birds and insects as indicators of rainfall seasonality. Entomological studies done in the Rwenzori region in Western Uganda showed that Stomoxys calcitrans breed during the onset of rains but are adversely affected by the dry season (Kangwagye 1974;Parr 1959). The onset of rains provides good conditions in open grazing areas with moist rotted dung that enables eggs to hatch and the pupae to emerge into adult flies (Parr 1959).…”
Section: ) Insectsmentioning
confidence: 99%
“…Entomological studies done in the Rwenzori region in Western Uganda showed that Stomoxys calcitrans breed during the onset of rains but are adversely affected by the dry season (Kangwagye 1974;Parr 1959). The onset of rains provides good conditions in open grazing areas with moist rotted dung that enables eggs to hatch and the pupae to emerge into adult flies (Parr 1959). In the dry seasons, cattle kraals moist with rotted cow dung and urine provide good conditions for breeding (Parr 1959).…”
Section: ) Insectsmentioning
confidence: 99%
See 1 more Smart Citation